Mitigating Lifestyle Disorders through Ayurveda - Dwivedi, Richa; Dr. Kshipra Rajoria (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: The rising prevalence of lifestyle diseases such as hypertension, diabetes, dyslipidemia, and obesity is alarming, particularly regarding cardiovascular health, which accounts for about 30% of global deaths. In India, the incidence of these disorders has surged due to rapid economic growth and Westernized lifestyles. Ayurveda, a holistic life science, offers effective strategies for preventing and managing these conditions through comprehensive dietary management, lifestyle modifications, detoxification methods like Panchakarma, and rejuvenation therapies. Material and methods: Material related is collected from Ayurvedic text including Bahatriye, Laghutrye,. The available commentaries of Ayurvedic samhitas has also been referred to collect relevant matter. Ayurveda addresses physical, psychological, and spiritual health, making it particularly relevant for lifestyle-related issues. Cardiovascular problems, categorized under Hridroga, highlight the connection between heart health and psychological well-being, illustrating how stress negatively impacts cardiac function. Unlike conventional Western medicine, which often focuses solely on physical symptoms, Ayurveda emphasizes identifying and treating root causes to promote overall wellness. A person's lifestyle reflects their psychological influences and early experiences, and disruptions in this balance lead to lifestyle disorders, which Ayurveda attributes to 'Prajnaparadha' (intellectual error). Discussion: By advocating for healthier habits through regimens like Dinacharya (daily routines) and Ritucharya (seasonal practices), Ayurveda supports detoxification and overall well-being.